Capsicum breeding strategies for anthracnose resistance - Mongkolporn, Orarat (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2018)
Capsicum, more commonly as chili or chili pepper, is an important global vegetable and spice crop. Anthracnose disease, caused by a complex of Colletotrichum species, is the major biotic stress limiting chili production in tropical and subtropical countries. Anthracnose disease mainly manifests itself as a post-harvest disease, resulting in large necrotic lesions on the fruit. This disease is mainly controlled by the application of a "cocktail" of fungicides as commercial resistant cultivars are not available. In recent years, insights into the complexity of the pathogen and the genomics of the host have been accomplished using cutting-edge molecular technologies. The author has been at the forefront of this technology revolution in Capsicum breeding through her research to understand the host and pathogen which has led to the development of new anthracnose resistant genotypes. Capsicum: Breeding Strategies for Anthracnose Resistance is structured based on a review of the origin and evolution of Capsicum, Capsicum genetic diversity and germplasm resources, the latest research in the biology and taxonomy of Colletotrichum pathogens of Capsicum, and the classic and molecular breeding for resistance in Capsicum to the suite of Colletotrichum pathogens that infect Capsicum globally. This book brings together knowledge on both the pathogen and the host, which is often overlooked when reviewing the breeding and genetics of a crop plant. It informs the facts behind breeding for resistance from both the host and pathogen perspectives.
OCLC-licensed vendor bibliographic record.
Keywords: Peppers -- Disease and pest resistance; Peppers -- Breeding; Anthracnose; MEDICAL / Pharmacology; SCIENCE / Life Sciences / Botany; TECHNOLOGY / Agriculture / General